HUBUNGAN PERILAKU BULLYING DENGAN SIKAP KOMUNIKASI INTERPERSONAL PADA SISWA KELAS X SP 6 SMK NEGERI 8 KOTA SURAKARTA TAHUN PELAJARAN 2025/2026 - Ratna Sari, Julia; Heru Sri Suryanti, Hera; Jawandi, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Julia Ratna Sari. THE RELATIONSHIP BETWEEN BULLYING BEHAVIOR AND INTERPERSONAL COMMUNICATION ATTITUDE AMONG STUDENTS OF CLASS X SP 6 AT SMK NEGERI 8 SURAKARTA CITY, ACADEMIC YEAR 2025/2026. This study aimed to determine the relationship between bullying behavior and interpersonal communication attitude among students of class X SP 6 at SMK Negeri 8 Surakarta City. The population consisted of 415 students of class X SP, with a sample of 105 students selected through cluster sampling. Data were collected through questionnaires, interviews, and documentation. Instrument try-out used construct validity and the Spearman-Brown reliability formula, while data were analyzed using the product moment correlation technique. The results showed a correlation coefficient of rxy = -0.537 with a p-value of 0.000 < 0.05, indicating a significant negative relationship between the two variables. Thus, the null hypothesis (Ho) stating that there is no relationship between bullying behavior and interpersonal communication attitude was rejected, while the working hypothesis (Ha) stating that there is a relationship between the two variables was accepted. These findings indicate that the lower the bullying behavior of students, the better their interpersonal communication attitude, and conversely, the higher the bullying behavior, the lower their interpersonal communication attitude.